2020
DOI: 10.1016/j.vhri.2020.07.455
|View full text |Cite
|
Sign up to set email alerts
|

PNS36 Cost-Benefit Analysis of Dental Prevention Programs for Children in Taiwan

Abstract: Objectives: Regulatory science (RS) grounds its value on enhancing regulatory capacity through developing and adopting scientific disciplines applicable to the evaluation of health-related products. While drug regulatory authorities (DRAs) are increasingly engaged with RS, their approaches have not been systemically examined. This research aimed to analyze the experiences of RS development based on a cross-country comparison guided by the logic modeling. Methods: DRAs in China (National Medical Products Admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of this study showed that compared with the control group, the benefits of applying PFS from both perspectives were greater than the costs (BCR >1), and the BCR was higher from the societal perspective. It is consistent with the findings in Taiwan that the application of PFS is more cost-effective compared to not sealing [Lai et al, 2020]. PFS has a protective effect on the teeth and prevents 16.06 million dental caries lesions in the PFMs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study showed that compared with the control group, the benefits of applying PFS from both perspectives were greater than the costs (BCR >1), and the BCR was higher from the societal perspective. It is consistent with the findings in Taiwan that the application of PFS is more cost-effective compared to not sealing [Lai et al, 2020]. PFS has a protective effect on the teeth and prevents 16.06 million dental caries lesions in the PFMs.…”
Section: Discussionsupporting
confidence: 90%
“…Studies generated Markov models [Quiñonez et al, 2005;Bertrand et al, 2011;Espinoza-Espinoza et al, 2019] and decision tree models [Halasa-Rappel et al, 2021] to focus on the costs and effects of PFS application on children's permanent molars. Cost-effectiveness analysis is mostly used, and fewer studies have conducted cost-benefit analysis [Lai et al, 2020] and cost-utility analysis [Bhuridej et al, 2007;Espinoza-Espinoza et al, 2019]. Although short-term analyses of the economics of PFS application have been conducted in some parts of China [Lai et al, 2020;Yang and Li, 2016], there is still a lack of high-quality evidence from China at the national level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation